Устройство для размыва осадков и перемешивания - Гаврилов П. М. Петр Михайлович; Гамза Ю. В. Юрий Вячеславович; Мацеля В. И. Владимир Иванович; Бараков Б. Н. Борис Николаевич; Томилин С. В. Сергей Викторович; Бочкарев В. А. Виталий Александрович
опубл. 20.08.13